4(14c-10d)-6(d+4c)=equation

Simple and best practice solution for 4(14c-10d)-6(d+4c)=equation equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(14c-10d)-6(d+4c)=equation equation:


Simplifying
4(14c + -10d) + -6(d + 4c) = equation
(14c * 4 + -10d * 4) + -6(d + 4c) = equation
(56c + -40d) + -6(d + 4c) = equation

Reorder the terms:
56c + -40d + -6(4c + d) = equation
56c + -40d + (4c * -6 + d * -6) = equation
56c + -40d + (-24c + -6d) = equation

Reorder the terms:
56c + -24c + -40d + -6d = equation

Combine like terms: 56c + -24c = 32c
32c + -40d + -6d = equation

Combine like terms: -40d + -6d = -46d
32c + -46d = equation

Solving
32c + -46d = aeinoqtu

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '46d' to each side of the equation.
32c + -46d + 46d = aeinoqtu + 46d

Combine like terms: -46d + 46d = 0
32c + 0 = aeinoqtu + 46d
32c = aeinoqtu + 46d

Divide each side by '32'.
c = 0.03125aeinoqtu + 1.4375d

Simplifying
c = 0.03125aeinoqtu + 1.4375d

See similar equations:

| 4(8u+8)=-4(20-12u) | | h=10+75t+-15t^2 | | x=55-3 | | h+5.1=-5.1 | | -9(d+2)-9=-20-13d-19 | | 8y+2x-24=0 | | Log(x)25=3 | | 2-15g=-8(3g-16)-5g | | 6+(-12)=7x-6-6x | | y+2.5=-8.1-6.3 | | 3x+32-3=7(5x+5) | | 0=-14v+14 | | 2x+ax=10 | | Y=-4x^2+5 | | x=(-(x-3))/(-1/2) | | .27-.02(x+1)=-.05(2-x) | | 3x+31=127 | | 3x^4-9x^3+7x^2-3x+2=0 | | x-0.1=3.3 | | 2k-12=4k | | -9x^2-61x+14=0 | | -2x=-2y+4 | | 2(h+9)-h=h+16 | | y-5=-1+7 | | 3x+12x-6=3(5x+7) | | x-1/8=15/8 | | 16-2t=3t+9 | | x-1/8=15/8= | | 12a-17=9 | | -2p=9 | | -10w+1=25 | | 4x+y-2=16 |

Equations solver categories